2016
DOI: 10.1080/10826084.2016.1188951
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Stigma Among People Who Inject Drugs

Abstract: The sample comprised 102 people who inject drugs. Internalized stigma was higher among participants who reported being depressed in the past month, and was also associated with greater severity of drug dependence and diminished self-esteem. There was no relationship between internalized stigma and shared use of needles or other injecting equipment in the past month. Conclusions/Importance: Findings underscore the need for further investigation of internalized stigma among people who inject drugs. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 23 publications
3
30
1
4
Order By: Relevance
“…Frequent experience of discrimination was also associated with one out of two mental health indicators and all three wellbeing indicators. This builds upon previous research demonstrating an overall link between discrimination and mental and physical health (Couto e Cruz et al, Unpublished results;Young et al, 2005;Cama et al, 2016;Treloar et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Frequent experience of discrimination was also associated with one out of two mental health indicators and all three wellbeing indicators. This builds upon previous research demonstrating an overall link between discrimination and mental and physical health (Couto e Cruz et al, Unpublished results;Young et al, 2005;Cama et al, 2016;Treloar et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have found links between stigma, discrimination, and the health and wellbeing of people who use drugs (Cama et al, 2016;van Boekel et al, 2013) and have highlighted the importance of reducing discrimination in health and social care contexts (Brener et al, 2010;Neale et al, 2008). However, beyond this initial evidence, there is limited understanding of whether frequency of discrimination impacts the health, wellbeing, and welfare of PWID.…”
Section: Introductionmentioning
confidence: 99%
“…In this latter respect the literature takes two main forms (although see, for example, Room, 2005). One form comprises highly specific studies on stigmatising practices in particular settings such as drug treatment services, hospitals and workplaces, on how individuals cope with stigma, and meta-analyses of these bodies of work (Barratt, 2011;Cama et al, 2016;Hathaway, 2011;Keyes et al, 2010;Kulesza et al, 2013;Livingston et al, 2011;Luoma et al, 2007;Radcliffe and Stevens, 2008;Rivera et al, 2014, Simmonds andCoomber, 2009;Treloar and Holt, 2006). This work explores and documents experiences of stigma, and the operations of stigmatising perspectives, and considers the impact of stigma on individuals as well as ways of tackling it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite increased availability and promising results of such treatments, many patients report experiences of HCV-related stigma and discrimination (Brener et al, 2015, Harris, 2009Zickmund et al, 2003). The aetiology of such stigma is multifaceted but includes fear of infectiousness (Fraser and Treloar, 2006), social aversion to illness (Maynard, 2006), and an association with illicit drug injecting (Cama et al 2016;Paterson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%